Automatic Gas Leakage Monitoring System Using MQ-5 Sensor - Baballe, Muhammad Ahmad; Magashi, Usman Yusuf; Garko, Bello Ibrahim; Umar, Abubakar Abdullahi; Magaji, Yunusa Rabiu; Surajo, Munzali (Review of Computer Engineering Research, 2021)
Safety plays a crucial role in today’s world, and an automatic safety system must be employed in environments like institutions, hospitals, homes, factories, and workplaces. One of the precautionary measures that must be taken to avoid the danger associated with gas leaks is to install a gas leak detection system in places that are at risk. This paper presents a liquefied petroleum gas (LPG) leakage monitoring system. The gas detector MQ-5 used in the design is responsible for measuring the gas that is leaking. An Arduino microcontroller acts as the brain of the whole system, controlling all the components in the design. If the gas sensor detects a gas leak, it will sound an alarm by means of a buzzer and will send SMS messages to the registered mobile numbers with the help of the GSM module. A liquid crystal display is used in the study to display the presence or absence of gas leakage.